2012
DOI: 10.1098/rspb.2012.1885
|View full text |Cite
|
Sign up to set email alerts
|

Social and extra-pair mating in relation to major histocompatibility complex variation in common yellowthroats

Abstract: Females are thought to gain better-quality genes for their offspring by mating with particular males. Genes of the major histocompatibility complex (MHC) play a critical role in adaptive immunity, and several studies have examined female mate choice in relation to MHC variation. In common yellowthroats, females prefer males that have larger black facial masks, an ornament associated with MHC variation, immune function and condition. Here we also tested whether mating patterns are directly correlated with MHC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 59 publications
3
54
2
Order By: Relevance
“…These MHC characteristics are consistent with the majority of other passerine MHC studies, which also reported multiple copies of MHC class I genes and pseudogenes Balakrishnan et al 2010;Borg et al 2011;Bollmer et al 2012;Sepil et al 2012;Wutzler et al 2012;Alcaide et al 2013). The minimum number of functional loci for the lark sparrow was estimated to be four based upon the number of unique functional sequences (alleles) identified in a single individual (Table 1).…”
Section: Lark Sparrow Mhc Class I Characterizationsupporting
confidence: 65%
See 1 more Smart Citation
“…These MHC characteristics are consistent with the majority of other passerine MHC studies, which also reported multiple copies of MHC class I genes and pseudogenes Balakrishnan et al 2010;Borg et al 2011;Bollmer et al 2012;Sepil et al 2012;Wutzler et al 2012;Alcaide et al 2013). The minimum number of functional loci for the lark sparrow was estimated to be four based upon the number of unique functional sequences (alleles) identified in a single individual (Table 1).…”
Section: Lark Sparrow Mhc Class I Characterizationsupporting
confidence: 65%
“…Furthermore, gene duplication events may further increase diversity through diversification of multiple gene loci (Walsh and Stephan 2001). Similar results have been reported for most other passerine species, including the great reed warbler , the common yellowthroat (Bollmer et al 2012), and the great tit (Sepil et al 2012).…”
Section: Lark Sparrow Mhc Class I Characterizationsupporting
confidence: 58%
“…This study adds to the accumulating body of evidence suggesting that the MHC class I genes in passerine birds often are highly duplicated and highly polymorphic [7, 8, 24, 36, 38, 52, but see 63]. Although many passerine species appear to have highly duplicated MHC class I genes (notable examples include great tits and willow warblers with 19 MHC class I loci [8, 36]) the present study has extended the upper known limit to 33 MHC class I loci in a passerine bird.…”
Section: Discussionmentioning
confidence: 96%
“…The cell-surface proteins encoded by MHC genes bind and present short peptides (antigens) derived from the processing of pathogens to lymphocyte T-cells, which triggers the adaptive branch of the immune system (Iwasaki & Medzhitov, 2010). MHC genes are also thought to play important roles in avian mate choice, although the conclusions of various studies have been mixed, in part because of the complexity of this redundant multigene family (e.g., Strandh et al, 2012; Bollmer et al, 2012; Juola & Dearborn, 2011; Knafler et al, 2012; Ekblom et al, 2004; Westerdahl, 2004). …”
Section: Introductionmentioning
confidence: 99%